First record of the Nile tilapia Oreochromis niloticus (Linnaeus, 1758), from the Shatt Al-Arab River, Southern Iraq - Al-Faisal , A.J.; Mutlak, F.M. (Mesopotamian Journal of Marine Sciences, 2022)
The exotic cichlid Oreochromis niloticus (Linnaeus, 1758) was first recorded from the Shatt Al-Arab River, at Basrah (Abu-al-Khasib), Iraq. This species was the third cichlid recorded in Iraq. O. aureus and Tilapia zillii have also been recorded for the region. Samples were collected by gill nets during November 2013 and April 2014. Specimens ranged from 192 to 292 mm total length and from 136.5 to 500.06 g. in weight. The Nile tilapia is characterized by having regular dark vertical stripes on the caudal fin, dorsal fin with 17-18 spines, 35-40 lateral line scales and 28-31gill rakers.